Evaluasi Aplikasi Inarisk Menggunakan Indeks Kepuasan Pengguna Berdasarkan Peraturan Menteri Pendayagunaan Aparatur Negara Dan Reformasi Birokrasi Nomor 14 Tahun 2017 - Findi Ayu Sariasih; Edhi Prayitno; Chaerul Bahri; Dhefine Armelsa; Fara Mutia (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
This study examines the satisfaction of the public towards the inaRISK application, based on the calculation of the Public Satisfaction Index using the guidelines outlined in the Minister of Administrative and Bureaucratic Reform Regulation No. 14 of 2017 regarding the public satisfaction survey on public service delivery. The findings reveal that the calculated index score is 83.46, falling within the range of 76.61 - 88.30, indicating a "B" level of service quality, categorized as Good. This suggests that overall, the inaRISK application is considered to be of good quality and is well-received by the public. The study further examines nine service indicators, finding that the highest satisfaction score is attributed to the Facilities and Infrastructure indicator, with an index score of 3.665 and a conversion score of 91.62. This indicates that users are satisfied with the consultation and complaint handling services provided by the inaRISK application (such as ease of filing complaints and follow-up actions). On the other hand, the lowest satisfaction score is observed in the Speed of Response indicator, with an index score of 3.170 and a conversion score of 79.26. In conclusion, this research shows that the inaRISK application receives positive feedback from the public, indicating good quality in public service delivery. However, there is room for improvement, particularly in terms of response speed, to enhance user satisfaction and overall performance of the application.